Performance Analysis In IoT Based Home Automation Using Hybrid RS-LDPC Codes - Ng, Lay Wei (Universiti Sains Malaysia, 2018)
Internet of Things (IoT) is no longer an idea that announces being the next big thing, but it is the thing. It has transformed the way people live. It connected the physical devices to the Internet and made them become more intelligent. In home automation system based on IoT, user-requested operations may have malfunction problems when bits error gets generated due to heavy noise in the fading channel. In order to address this problem, this work starts to evaluate the performance of different code rates for LDPC codes used in the preparation for Hybrid combination of Reed-Solomon (RS) and Low-Density Parity-Check (LDPC) codes. The thesis proposes an error detection and correction algorithms using Hybrid RS-LDPC codes for the channel encoding and decoding in the home automation system. The performance of Hybrid RS-LDPC codes is evaluated in term of decoding efficiency and processing time using Raspberry Pi board. The input information is the text messages that transmitted from webpage. The transmitted messages are passed though the RS encoder and followed by LDPC encoder. Then, the generated codeword is sent over a fading channel with less than or equal to 0.9 SNR. Hence, the codeword is decode by LDPC decoder , then followed by RS decoder to obtain the received messages with error-free. Code rate of 1/3 with 27% of decoding efficiency and 11.9s of time taken for decoding process is more suitable than 1/4 to implement into the LDPC codes in Hybrid codes when SNR=0.9. The error detection and correction algorithms implemented in home automation system is successfully developed by encoding and decoding the text messages that transmitted from webpage to Raspberry Pi board using Python and HTML programming language. The efficiency decoding for Hybrid RS-LDPC codes is 11% more than the LDPC codes when SNR=0.9 and 50 of characters length transmitted for total 100 samples analysed. The Hybrid RS-LDPC codes provide better decoding performance than solo FEC codes (such as LDPC codes).